Research of behaviors of continuous GNSS station by signal analysis methods (2018)
Continuously Operating Reference Station (CORS) networks consisting of multiple GNSS systems have been set up and operating in many developed countries. In Turkey, CORS-TR has been operating. The aim of CORS-TR is a fast, correct, and reliable collection of all kinds of geographic data, thus, speeding up the activities of cadastre, assuring organized urbanization, constituting the spatial infrastructure for relevant works of e-government, and monitoring plate tectonics. Therefore, in this paper, we investigated 788 days of linear and periodic of AKHR, BEYS, CIHA, KAMN, YUNA, AKSI and KNYA CORS-TR stations by linear trend analysis and Wavelet Transform in located in the Central Anatolia Region of Turkey. As a result of trend analyses of time series, it was determined that except a single station (KAMN), other stations were moving in the Southwest direction (17.78 mm/year). This finding is consistent with the region’s tectonic plate movements. In the periodical analyses, stations’ daily, monthly, seasonal, annual and even biennial movements resulting from atmospheric and hydrologic loading, climatic and other effects were revealed. Moreover, Detail (D) component, which protects the largest percentage of energy, was determined by calculating the energy spectrum. Energies of detail components are similar in horizontal, and especially D7-D8 have the highest energy. However, the components obtained the maximum energy was varied in Up coordinate time series. These results indicate that stations of CORS-TR network located in Central Anatolia were rather stable and able to be providing reliable, accurate and continuous data for national and international studies to be conducted in many fields.